Origins of the Faculty of Theology. Historical Context and Foundational Breve (Teología, 2015)
This article focuses on the origins and development of the Faculty of Theology of the Argentine Catholic University in occasion of its centenary anniversary. Taking into account the background of the University in Argentina in the XVII century, the author concentrates his attention in the circumstances and events around the foundational Brief of 1916 and goes through the first moments of its academic life until the beginning of the Second Vatican Council.
Keywords: Faculty of Theology; Formation of the Clergy; Theological Education; Latin American Plenary Council